FairMOT: On the Fairness of Detection and Re-Identification in Multiple Object Tracking - Zhang, Yifu; Wang, Chunyu; Wang, Xinggang; Zeng, Wenjun; Liu, Wenyu (International Journal of Computer Vision (to appear), 2021)
.